Pleistocene slip rates on the Boconó fault along the North Andean Block plate boundary, Venezuela. Issue 7 (1st July 2017) - Pousse‐Beltran, Lea; Vassallo, Riccardo; Audemard, Franck; Jouanne, François; Carcaillet, Julien; Pathier, Erwan; Volat, Matthieu
Abstract: The Boconó fault is a strike‐slip fault lying between the North Andean Block and the South American plate which has triggered at least five M w  > 7 historical earthquakes in Venezuela. The North Andean Block is currently moving toward NNE with respect to a stable South American plate. This relative displacement at ~12 mm yr −1 in Venezuela (within the Maracaibo Block) was measured by geodesy, but until now the distribution and rates of Quaternary deformation have remained partially unclear. We used two alluvial fans offset by the Boconó fault (Yaracuy Valley) to quantify slip rates, by combining 10 Be cosmogenic dating with measurements of tectonic displacements on high‐resolution satellite images (Pleiades). Based upon a fan dated at >79 ka and offset by 1350–1580 m and a second fan dated at 120–273 ka and offset by 1236–1500 m, we obtained two Pleistocene rates of 5.0–11.2 and <20.0 mm yr −1, consistent with the regional geodesy. This indicates that the Boconó fault in the Yaracuy Valley accommodates 40 to 100% of the deformation between the South American plate and the Maracaibo Block. As no aseismic deformation was shown by interferometric synthetic aperture radar analysis, we assume that the fault is locked since the 1812 event. This implies that there is a slip deficit in the Yaracuy Valley since the last earthquake ranging from ~1 to 4 m, corresponding to a M w 7–7.6 earthquake. This magnitude is comparable to the 1812 earthquake and to other historical events along the Boconó fault. Key Points: We measured the two Pleistocene slip rates along the Boconó fault using 10 Be dating and Pleiades images (5.0–11.2 mm yr −1 and <20 mm yr −1 ) Boconó fault in the Yaracuy Valley accommodates 40 to 100% of the relative displacement between the Maracaibo Block and the South American plate The slip deficit in the Yaracuy Valley ranges from 1 to 4 m along the Boconó fault since the M WI 7.4 event in 1812